Descrição de Hisonotus sp. n (Siluriformes: Loricariidae: Hypoptopomatinae), da Bacia do Alto Paraguai, MT, com inferências acerca de suas relações filogenéticas - Freitas Junior, Djair Sergio de (2013)
Hisonotus sp. n is the first specie of the genus to be described from the Paraguay river basin, Mato Grosso. The description is made on the basis of specimens collected in the Serragem II river, tributary of Cuiabá river. The new taxon is distinguished from its congeners by having a unique pattern of colour in the body, sexual dimorphism presented by a fleshy flap on the first ray of pelvic fins of males and a pattern of macules on the caudal peduncle. Through morphological and osteological data entered into a matrix of characters presents the phylogenetic allocate of the new taxon in Hisonotus and trace-if measurement of phylogenetic genus based on current knowledge of their relationships within Hypoptopomatinae. The characters were subjected to phylogenetic parsimony analysis. A cladogram of the strict consensus was generated, where they were found three trees maximally parcimonious with length of 263 steps, consistency index (CI) of 0.295 and retention index (RI) of 0.639. Through this study the new species confirms the complexity and morphological variability of the genus, positioning itself as the sister taxon of both other species of Hisonotus, as well as of the species that make up the tribe Hypoptopomatini.